Parameter estimation to study the immediate impact of aortic cross‐clamping using reduced order models. (14th November 2019) - Ventre, Jeanne; Politi, M. Teresa; Fernández, Juan M.; Ghigo, Arthur R.; Gaudric, Julien; Wray, Sandra A.; Lagaert, Jean‐Baptiste; Armentano, Ricardo; Capurro, Claudia; Fullana, José Maria; Lagrée, Pierre‐Yves
Abstract: Aortic cross‐clamping is a common strategy during vascular surgery, however, its instantaneous impact on hemodynamics is unknown. We, therefore, developed two numerical models to estimate the immediate impact of aortic clamping on the vascular properties. To assess the validity of the models, we recorded continuous invasive pressure signals during abdominal aneurysm repair surgery, immediately before and after clamping. The first model is a zero‐dimensional (0D) three‐element Windkessel model, which we coupled to a gradient‐based parameter estimation algorithm to identify patient‐specific parameters such as vascular resistance and compliance. We found a 10% increase in the total resistance and a 20% decrease in the total compliance after clamping. The second model is a nine‐artery network corresponding to an average human body in which we solved the one‐dimensional (1D) blood flow equations. With a similar parameter estimation method and using the results from the 0D model, we identified the resistance boundary conditions of the 1D network. Determining the patient‐specific total resistance and the distribution of peripheral resistances through the parameter estimation process was sufficient for the 1D model to accurately reproduce the impact of clamping on the pressure waveform. Both models gave an accurate description of the pressure wave and had a high correlation ( R 2 > .95) with experimental blood pressure data. Abstract : We used two reduced order models (0D and 1D models) to investigate the immediate impact of aortic clamping during surgery, on the vascular properties (resistance and compliance). We recorded continuous invasive pressure signals to assess the validity of the models during aneurysm repair surgery immediately before and after clamping. Both the 0D and 1D models brought relevant information at the systemic and arterial scale respectively, allowing identification of powerful indicators for diagnosis and decision‐making in critical care scenarios.